Sensibilidad postoperatoria al cambio de una amalgama a una resina compuesta considerando el umbral del dolor en los estudiantes de la Universidad Nacional de Loja en las edades comprendidas entre 18 a 30 años en el periodo marzo-julio 2015 - Vaca Merino, Evelyn Lizbeth (2015)
This study was conducted in order identify the presence of postoperative sensitivity to change of an amalgam restoration with a composite resin considering the pain threshold in the students of the National University of Loja aged between 18-30 years in the March to July period of 2015 a quantitative, transversal, prospective and descriptive study; where 25 students who had teeth with amalgam restorations, for a period of approximately five years which were clinically and radiographically evaluated and concluded that the change of a composite resin material was included requiring performed; information through the Dental Clinic History and within this the Visual Analogue Scale (VAS) was used to determine the pre and postoperative sensitivity by applying a thermal stimulus of heat and cold for a certain time was collected. The data obtained after susceptibility testing were analyzed, concluding that 100% of subjects had postoperative pre sensitivity and mild to moderate intensity in a measured time interval of 10 seconds to 20 seconds cold to heat; also we reiterate that postoperative sensitivity was higher; 52%, after the change of the restoration and applied thermal stimuli. Keywords: Postoperative sensitivity, amalgam, composite resin.